CONTRACT REGULATION OF ECONOMIC PROCESSES AS A TOOL OF EFFICIENT MANAGEMENT (Development Service Industry Management, 2023)
In the conditions of the post-industrial development of market relations, the relevance of research related to the use of contractual regulation of economic processes has increased tremendously. This specific feature, we believe, is caused primarily by the limitation of the institutional capabilities of generally recognized approaches to explaining the depth and essence of socio-economic problems in our country. In this regard, contractual regulation should be considered as an effective means of increasing the effectiveness of the work of market agents by integrating the interests of the main participants in institutional relations in the context of maximizing the total value and rational use of limited resources.The purpose of the article is to justify the theoretical and methodological principles of the effective use of contractual regulation of economic processes in Ukraine in the context of the formation of an effective management system.  The article identifies the state, institutional problems and prospects of using contractual regulation in the domestic economy. The main principles and types of economic contracts in the context of building an effective management system are studied. It is proposed to use relational contractual regulation of economic processes in order to maximize the total value of market agents and counteract opportunistic behavior patterns.The economic potential of the national economy significantly depends on effective contractual regulation as a tool for managing economic processes, which contains hidden institutional reserves. It has been established that modern contractual regulation, within the framework of the implementation of the market economic paradigm, is a complex socio-economic phenomenon that forms the concept of effective relations between business entities. At the same time, the essence of contractual regulation is due to the formation of the integrative effect of the agreement between two or more market agents, which identifies the system of actions (or inaction) and the main mechanisms of responsibility of the participants of the agreement in the event of institutional conflicts. It is also quite obvious that in the economy the determining role belongs to relational contractual regulation as the leading tool for maximizing the total value.
Keywords: contract; opportunism; management; efficiency; contract regulation; conflict; economic processes; market agent